PELAKSANAAN USAHA KESEHATAN SEKOLAH DI SEKOLAH DASAR NEGERI SE KECAMATAN SUMBERLAWANG KABUPATEN SRAGEN TAHUN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This  survey  research  aimed  to  det ermine  the  impl ementat ion  of  the  School  Heal th  Unit    in  a  Districtelementary  school   Sumberlawang  Sragen  Year  2012/2013.  This  st udy  used  a  questionnaire  instrument   i sclosed.  The  populat i on  in  this  st udy  were  28  elementary  school   in  the  District  Sumberl awang  Sragen.Sampl ing  was  done  by  total   sampling,  which  is  28  El ementary  School   in  District   Sumberlawang.  Thequest ionnaire  has  previousl y  been  t est ed  in  SD  in  Batang  regency.  Af ter  val id  and  reliable  then  thequest ionnaire  used  in  the st udy.  The resul ts of this  research is the  i mplement ation of t he  School Healt h Uni t  ina  Dist rict  element ary  school  Sumberkawang  Sragen  wi th  an  average  percentage  of  76.25%,  shows  have  beengoing  well .  Implementation  of the School  Heal th  Unit  (UKS)  is inf l uenced by  a good three  indicat ors, namel yhealt h education with t he  percentage of 83.10%, good health care with t he percentage of 66.30%, and  fosteringa  healthy  environment  79.30%.  Based  on  the  results  of  this  study  concl uded  that  the  implementation  of  theSchool Healt h  Unit   District   Sumberl awang  se  Sragen year 2012/2013 has been going  wel l.